Implementasi Metode Imla’ Manqul Dalam Meningkatkan Kemampuan Menulis Huruf Arab Di TPQ Tanwirut-Thullab Panikel, Kampung Laut, Cilacap - Indana Zulfa; Robingun Suyud El Syam (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to: 1) Determine the best way to apply the imla' manqul method to improve the ability to write Arabic letters in TPQ Tanwirut-thullab Panikel Kampung Laut Cilacap; and 2) Identifying factors that facilitate or hinder the application of the imla' manqul method to improve the ability to write Arabic letters at TPQ Tanwirut-thullab Panikel Kampung Laut Cilacap. Qualitative methods are used in this thesis. Data collection was carried out through observation, interviews and documentation techniques. Data collection analysis is used to examine the collected data, which includes data reduction, data presentation, and drawing up conclusions. The research findings yielded the following conclusions: 1) The use of the imla manqul method by TPQ Tanwirut-thullab to improve students' Arabic letter writing skills. The imla manqul technique is used for lesson planning, the imla manqul method for implementation, and the manqul method for evaluating learning at the Cilacap Laut Village Panikel . Based on the great enthusiasm of students in participating in learning activities at TPQ Tanwirut-thullab, it can be concluded that the imla manqul method and the ability to read Arabic letters at TPQ Tanwirut-thullab are quite good and are working well. This shows that students are aware of their abilities and are motivated to become more proficient in reading Arabic script. 2) Factors that encourage and hinder the application of the imla manqul method at TPQ Tanwirut-thullab Panikel Kampung Laut Cilacap to improve Arabic letter writing skills. The following factors support the use of the Imla Manqul method to help students become more proficient in writing Arabic letters: a) The teachers at TPQ Tanwirut-thullab have the necessary experience, especially in the field of religious knowledge; b) Students are enthusiastic about participating in learning activities at school; and c) A peaceful and friendly school environment helps students concentrate when reciting the Koran. Meanwhile, the obstacles to the TPQ Tanwirut-thullab Panikel Kampung Laut Cilacap using the imla manqul method are as follows: a) Each student has a unique learning capacity. This can be seen from how quickly they achieve their goals. b) At TPQ Tanwirut-thullab, teacher tardiness is a problem that needs to be addressed immediately. Panikel, c) Infrastructure at TPQ Tanwirut-thullab, where one of the things that hinders the effectiveness of learning is the lack of facilities and infrastructure.